STM Images of Anionic Defects at CeO2(111)—A Theoretical Perspective - Wolf, Matthew J.; Castleton, Christopher W. M.; Hermansson, Kersti; Kullgren, Jolla (Frontiers in Chemistry, 2019)
We present a comprehensive simulated reference companion to the appearance and properties of plausible candidates for the anionic defects observed in scanning tunnelling microscopy (STM) experiments on CeO2 (111), a prototypical reducible oxide surface, in order to assist with experi- mental characterisation. The simulations are based on density functional theory (DFT) and cover oxygen vacancies, fluorine impurities and hydroxyl groups in the surface and sub-surface layers. In the surface layer, all three appear as missing spots in the oxygen sublattice in filled state simulated STM images, but they are distinguishable in empty state images, where surface oxygen vacancies and hydroxyls appear as, respectively, diffuse and sharp bright features at oxygen sites, while flu- orine defects appear as triangles of darkened Ce ions. In the sub-surface layer, all three defects present more complex patterns, with different combinations of brightened oxygen ion triangles and/or darkened Ce ion triangles, so we provide image maps to support experimental identifica- tion. We conclude that identification of defects in STM images requires careful comparison of both filled and empty state images, as well as other properties such as their distributions and diffusion rates.